Pragmatic Perspectives on Teacher-Child Interaction in Religio-Cultural Early Childhood Education - Uctuvia, Vina; Hanan, Abdul; Ismail, Muhamad (Mozaic : Islam Nusantara, 2025)
Early Childhood Education is a formative stage in children’s cognitive, social, and moral development, where teacher–child interaction contributes not only to learning outcomes but also to the internalization of cultural and religious values. In pesantren-based educational settings, these interactions are shaped by local traditions and Islamic norms. This study aims to explore the pragmatic dimensions of teacher–child interaction in a pesantren-affiliated kindergarten in Babakan, Ciwaringin, Cirebon, an area recognized for its strong Islamic educational heritage. A qualitative descriptive approach was applied. Data were collected through classroom observations, audio recordings, and semi-structured interviews with teachers. The data were transcribed and analysed using frameworks from speech act theory, politeness theory, and conversational implicature to identify the forms and functions of teacher communication. The findings show that directive speech acts are the most dominant, reflecting the teacher’s central role in classroom management, moral guidance, and ritual instruction. Expressive and representative speech acts are frequently used to provide praise, encouragement, and knowledge, while commissive and declarative acts, though less common, perform important pedagogical and spiritual functions, such as shaping discipline and reinforcing religious practices. This research contributes to pragmatics by extending its application to religio-cultural education and offers insights for educators and policymakers in designing communication strategies that are both effective and culturally responsive.